The Emerging Role of Rho Guanine Nucleotide Exchange Factors in Cardiovascular Disorders: Insights Into Atherosclerosis: A Mini Review - Li, Mengqi; Jiao, Qingzheng; Xin, Wenqiang; Niu, Shulin; Liu, Mingming; Song, Yanxin; Wang, Zengguang; Yang, Xinyu; Liang, Degang (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is a leading cause of cardiovascular disease, and atherosclerotic cardiovascular disease accounts for one-third of global deaths. However, the mechanism of atherosclerosis is not fully understood. It is well-known that the Rho GTPase family, especially Rho A, plays a vital role in the development and progression of arteriosclerosis. Rho guanine nucleotide exchange factors (Rho GEFs), which act upstream of Rho GTPases, are also involved in the atheromatous pathological process. Despite some research on the role of Rho GEFS in the regulation of atherosclerosis, the number of studies is small relative to studies on the essential function of Rho GEFs. Some studies have preliminarily revealed Rho GEF regulation of atherosclerosis by experiments in vivo and in vitro. Herein, we review the advances in research on the relationship and interaction between Rho GEFs and atheroma to provide a potential reference for further study of atherosclerosis.